Bukkal bölgede pleomorfik adenoma: bir olgu sunumu - Defne Akpinar; Esma Boysan; Filiz Tahtabas; Mustafa Ozturk (Cumhuriyet University, 2011)
Introduction: Pleomorphic adenoma is most common tumor (%50) of the major and minor salivary glands. Seventy percent of the tumors of the minor salivary glands are pleomorphic adenomas, and the most common intraoral site is the palate, followed by the upper lip and buccal mucosa. The tumor is usually solitary and presents as a slow growing, painless, firm single nodular mass. Case report: A 56 -year-old female with a painless buccal mass that slowly increased in size was referred Department of Oral and Maxillofacial Surgery of Dentistry Faculty of Gazi University. Clinic examination and radiographic evaluation was determined painless, firm and extraoral expansive mass in the right buccal region. Lesion was enucleationed with its capsule. Histologic analysis confirmed the diagnosis of pleomorphic adenoma with no carcinomatous foci. The 24-month follow up showed good healing of the buccal mucosa. Conclusion: Through the present case report and review literatures, it is suggested that the minor salivary gland tumors are characterized by the higher incidence benign tumors, especially of pleomorphic adenoma. ÖZET Giriş: Pleomorfik adenoma majör ve minör tükürük bezlerinin en yaygın (%50) görülen tümörüdür. Minör tükürük bezi tümörlerinin %70'ini pleomorfik adenomalar oluşturur ve en sık görülen intraoral bölge palatinaldir, üst dudak ve bukkal mukoza bu sıralamayı takip eder. Bu tümör genellikle tek taraflı ve yavaş büyüme gösteren, ağrısız, katı kitle şeklindedir. Olgu: 56 yaşındaki bayan hasta bukkal bölgede büyüklüğü yavaşça artan ağrısız bir kitle ile Gazi Üniversitesi Diş Hekimliği Fakültesi Ağız, Diş, Çene Hastalıkları ve Cerrahisi Anabilim dalına başvurmuştur. Yapılan klinik ve radyolojik muayenede sağ bukkal bölgede; palpasyonda ağrısız, sert ve ekstraoral ekspansif kitle tespit edilmiştir. Lezyon kapsülüyle birlikte enükle edilmiştir. Histolojik tetkikler, karsinomatöz odaksız pleomorfik adenoma teşhisini doğrulamıştır. 24 aylık takipte bukkal mukoza iyi bir iyileşme göstermiştir. Tartışma: Sunulan olguda ve gözden geçirilen literatürler de minör tükürük bezi tümörlerinin, özellikle pleomorfik adenomanın daha yüksek benign tümör insidansıyla karakterize olduğunu desteklemektedir. Anahtar kelimeler: Tükürük bezi tümörleri, pleomorfik adenoma, bukkal bölge